If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(z + -8) + 7 = 5(z + 2) + -3z + -19 Reorder the terms: 2(-8 + z) + 7 = 5(z + 2) + -3z + -19 (-8 * 2 + z * 2) + 7 = 5(z + 2) + -3z + -19 (-16 + 2z) + 7 = 5(z + 2) + -3z + -19 Reorder the terms: -16 + 7 + 2z = 5(z + 2) + -3z + -19 Combine like terms: -16 + 7 = -9 -9 + 2z = 5(z + 2) + -3z + -19 Reorder the terms: -9 + 2z = 5(2 + z) + -3z + -19 -9 + 2z = (2 * 5 + z * 5) + -3z + -19 -9 + 2z = (10 + 5z) + -3z + -19 Reorder the terms: -9 + 2z = 10 + -19 + 5z + -3z Combine like terms: 10 + -19 = -9 -9 + 2z = -9 + 5z + -3z Combine like terms: 5z + -3z = 2z -9 + 2z = -9 + 2z Add '9' to each side of the equation. -9 + 9 + 2z = -9 + 9 + 2z Combine like terms: -9 + 9 = 0 0 + 2z = -9 + 9 + 2z 2z = -9 + 9 + 2z Combine like terms: -9 + 9 = 0 2z = 0 + 2z 2z = 2z Add '-2z' to each side of the equation. 2z + -2z = 2z + -2z Combine like terms: 2z + -2z = 0 0 = 2z + -2z Combine like terms: 2z + -2z = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5x-4(-3x+5)=-3 | | 10+9q=12+8q | | 28x-2=110 | | 2(x-6)=42 | | (4x+1)-7=22 | | 13+(2-x)=-6 | | 2x-2=110 | | 6x+23=16x-97 | | 5(x+6)-17= | | 2x-(5)=4x-(1) | | X^2+2kx+4k=0 | | 12x-8=-56 | | x+3y=360 | | -5(8n+3)= | | 6x+6=3x+33 | | 10+7x+52=x | | 21x+1+53=180 | | 5x+10=-5 | | 11-9x=104-30x | | 9x^2-121= | | 2z+7z+5z-1= | | 4x+32=11x-94 | | y^4-2y^2-8=0 | | 3x-6x+5x-9x= | | (x*5)+(.1x*15)=3260 | | 6x-3-2x=17 | | (48-3)/5=x | | s=.5gt | | 9(q+2)= | | 5e+8=56 | | 4x=11-3 | | 7x-4=-2x+1+9 |